STUDI TENTANG ANALISIS KINERJA PUTERA DAERAH SEBAGAI ANGGOTA DPRD KABUPATEN KARIMUN PERIODE 2014-2019 - Jefri Jefri; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is done to know about the performance of regional sons and the factors that affect to the performance of regional sons as DPRD members Karimun district, period 2014 - 2019. anguage problem formulation in this research is to know the performance of regional sons and the factors that affect of their performance as DPRD members in Karimun district, period 2014-2019. The benefit of this research is became reference for society to determine the demeanor of politic in the next general election. This research has done in April-July 2020. The samples in this research are 100 respondents that chosen by purposive sampling. The data was gotten by ditributed the questionnare, interview and documentation.The researcher was used quantitative descriptive methode to analyse the data.Based on the result of respondents recapulation, the overall is 64.41 % which the interval 61 % - 80 % are in well catehory. The almost of respondents answered that the factors that affect the regional sons performance is lack of communication between the regional sons and society.Key Words: Regional Sons, DPRD